Wood anatomical features of Anacardiaceae from Malaysia - Abdullah Siam, Nordahlia; Abdullah, Nor Azahana; Uyup, Mohd Khairun Anwar; Che Amri, Che Nurul Aini; Ahmad Juhari, Muhammad Amirul Aiman; Talip, Noraini (North Carolina State University, United States, 2023)
This study examined the anatomical features of Anacardiaceae from Malaysia. A total of 31 species from 13 genera of the family Anacardiaceae in Malaysia were obtained from Kepong Xylarium (KEPw), Forest Research Institute Malaysia. The genera in Anacardiaceae were distinguished based on anatomical features. The diagnostic anatomical features that were used to separate the genera are scalariform perforations plates present in Campnosperma, larger rays in Pentaspadon and Spondias, and radial canals in some genera. Mineral inclusion, i.e., crystals and silica also could be diagnostic features to distinguish the genera in Malaysian Anacardiaceae; silica was observed in Gluta, Parishia, and Swintonia. Anatomical features could be used as indicators to the other wood properties and lead to potential usage of timber in Anacardiaceae. However, the presence of druses in individual Toxicodendron succedaneum indicated its adaptation to the local microclimatic conditions.